A case of laparoscopic surgery for endometrial cancer in a patient previously treated with a transvaginal mesh procedure for pelvic organ prolapse - Kiyoshi Yoshino; Eiji Kobayashi; Masayuki Endo; Mamoru Kakuda; Aiko Okada; Takuji Tomimatsu; Kenjiro Sawada; Masahiko Takemura; Tadashi Kimura (Wolters Kluwer Medknow Publications, 2017)
Transvaginal mesh (TVM) surgery is an effective treatment option for women with pelvic organ prolapse (POP). Because the TVM procedure preserves the uterus, it is possible for endometrial cancer to occur at a later date. We herein present the first report of such an endometrial cancer, diagnosed well after TVM surgery for POP, and the use of laparoscopic surgery to conduct a simple total hysterectomy to treat it. Keywords: endometrial cancer, laparoscopic surgery, pelvic organ prolapse, transvaginal mesh